Efektivitas Edukasi Gizi Seimbang dalam Mengubah Perilaku Nutrisi Wanita Prakonsepsi untuk Pencegahan Stunting - Hidayati, Tutik; Iis Hanifah (Jurnal Kebidanan Malakbi, 2025)
Preparation for a healthy pregnancy should be prepared at least three to six months before pregnancy occurs. Adequate nutritional intake during the preconception period is the start of a healthy pregnancy and prevents stunting. One effort to convey nutritional knowledge to preconception mothers is through nutrition education. Through preconception nutrition education, a person's knowledge will increase, which will then have implications for their behavior in fulfilling preconception nutrition. This study aims to analyze the effect of balanced nutrition education on nutritional fulfillment behavior in an effort to prevent stunting in preconception mothers. The research design used was cross-sectional. The population was all preconception women in Gading Village, Probolinggo, totaling 67 people. The sample was determined using a simple random sampling technique and obtained 46 respondents. The research data were analyzed using the Wilcoxon statistical test. The analysis results showed a P value of 0.000, indicating that there is an effect of balanced nutrition education on nutritional fulfillment behavior in an effort to prevent stunting. Balanced nutrition education during the preconception period for expectant mothers is very necessary in improving good behavior in fulfilling balanced nutrition as an effort to prevent stunting from the preconception period.